Flicker light stimulation enhances the emotional response to music: a comparison study to the effects of psychedelics - Montgomery, Caspar; Amaya, Ioanna Alicia; Schmidt, Timo Torsten (Frontiers in Psychology, 2024)
Flicker light stimulation (FLS) is a non-pharmacological method of inducing altered states of consciousness (ASCs), producing hallucination-like phenomena as well as effects extending beyond the visual modality, including emotional effects. Research into the psychological and neural mechanisms of FLS is still in its infancy, but can be informed by research into other methods of inducing ASCs. For instance, research on classic psychedelics has reported enhancement of emotional responses to music. Here, we test to what degree FLS might also enhance the emotional response to music, using a study protocol designed to resemble a previous study on the effects of LSD as closely as possible, to allow for comparison of effect sizes across modalities and inform future research into FLS as an ASC-induction method. Twenty participants listened to emotionally evocative music in two conditionswith and without FLSand reported on their emotional response to the music. FLS showed a significant enhancing effect on reported music-evoked emotion, especially emotions relating to 'Joyful Activation'; additionally, we found that the experienced intensity of FLS correlated with reports of higher levels of emotional arousal. These findings motivate further research into FLS as a method for inducing ASCs and into the interactions between visual phenomena and music-evoked emotion.